A view at the university theatrical teaching on the road to a post-pandemic period - Coveñas, Victor (2022)
Education is a process in constant change and research. Moreover, in the field of the arts, it is important, especially in the Peruvian context, to see how the educational dynamics are being given in the context of university teaching around theater, since in recent years there has been a notable increase in institutions that offer this type of degree. With the arrival of the pandemic, this brought changes in educational methodologies and processes in various fields and clearly, one of the most affected was the university one. This document aims to review the educational programs offered by educational institutions in theater with university degree in the city of Lima in Peru, the changes that they suffered with the arrival of the pandemic and the horizons that they can take now that we are in a new circumstance as a society.